If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -6x = -12 + -4x Solving 6 + -6x = -12 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 6 + -6x + 4x = -12 + -4x + 4x Combine like terms: -6x + 4x = -2x 6 + -2x = -12 + -4x + 4x Combine like terms: -4x + 4x = 0 6 + -2x = -12 + 0 6 + -2x = -12 Add '-6' to each side of the equation. 6 + -6 + -2x = -12 + -6 Combine like terms: 6 + -6 = 0 0 + -2x = -12 + -6 -2x = -12 + -6 Combine like terms: -12 + -6 = -18 -2x = -18 Divide each side by '-2'. x = 9 Simplifying x = 9
| 180=(3x+y-10)+x+5 | | 180=3x+y-10+x+5 | | N-25=5 | | x+6+x+9+x+3=180 | | -7=3w-4 | | 11x-12=6x-2 | | 15b^2+10b-8= | | 3(n-6)=8+4n | | .75x+8=x | | 0=x*2-x-30 | | -6=y+3 | | 10+4x=-14+6x | | 15b^2+10b-8=0 | | .75x+8=f(x) | | u-5=-8 | | sin(4x)=1 | | 5=-21+3t | | 6+w=-2 | | (7x+4)(3x+9)= | | y=226-33x | | -36+6x=12 | | 3.6x+8=26 | | n-10=-27 | | 1.25g+4=13.5 | | a^2-x=0 | | 12-4h=6 | | j-(-17)=30 | | 5-3*x=20 | | t+13.4=-4.5 | | 1p-5=8 | | 4(p+5)=7 | | 36t^2=9 |